A RETROSPECTIVE ANALYSIS OF THE CLINICAL COURSE OF ACUTE APPENDICITIS ON THE BACKGROUND OF LIVER CIRRHOSIS AND ITS COMPLICATIONS - Abidov U.O; Ruziboev A.F (TADQIQOTLAR, 2025)
Resume Acute appendicitis (AA) is one of the most common urgent surgical diseases, which in conditions of cirrhosis of the liver (LC) leads to serious problems in diagnosis and treatment. Immunodeficiency, blood clotting disorders, ascites, and portal hypertension, characteristic of LC, aggravate the course of AA. Between 2017 and 2024, 64 patients with AA were analyzed. The study included a retrospective analysis (24 patients) and a prospective follow-up (40 patients). In addition to standard laboratory tests, patients with LC underwent biochemical liver examination and modern instrumental diagnostic methods (MRI). It has been established that with LS, AA often manifests itself with atypical symptoms. The majority of patients (87.5%) had decompensated LC. The phlegmonous form of AA was diagnosed in 50% of cases, catarrhal – in 37.5%, gangrenous – in 12.5%. Severe forms of AA were more often registered against the background of decompensated LC. Postoperative complications were high, and mortality was 25%. The analysis confirmed the importance of an individual approach in the diagnosis and treatment of AA in patients with LC. Improved surgical tactics and enhanced postoperative monitoring can help reduce complications and mortality.